# PHI constant

1. Jan 26, 2013

### Sciencer

Hi,

In the equation
y(x,t) = ym * sin(kx - wt - PHI)

I thought I understand why we have that phase constant atleast mathmetically but after thinking about it I don't think I understand it completely like here in my book it says the phase constant moves the wave forward or backward in space or time. Now lets say
we have wave at t = 0 and x = 0;

we would have y(x,t) = ym * sin(-PHI) that wouldn't really move it forward or backward in space or time if we had y(x,t) = ym + PHI then yeh it would have but I don't see how it would moves it backward or forward in that case ?

I can see how they derived
y(x,t) = ym * sin(kx - wt) but that PHI keeps confusing me.

2. Jan 26, 2013

### Philip Wood

You might try sketching a 'snapshot' of the wave (that is a graph of y against x) at t = 0, first for the case $\phi$ = 0, then for the case $\phi$ = $\pi$/2. The shift (in the x direction) of the wave profile brought about by $\phi$ should then be clear.

The purpose of including $\phi$ is so we have an equation which fits the general case: when y doesn't happen to be zero when x = 0 and t = 0. [An alternative, sometimes permissible, sometimes not, is to choose our zero of time (or of x) expressly to ensure that y = 0 and $\frac{\partial y}{\partial x} > 0$ when t = 0 and x = 0. Then we don't have to bother with $\phi$.]